Identification of a Membrane Protein Required for Lipomannan Maturation and Lipoarabinomannan Synthesis in Corynebacterineae - Cashmore, Tamaryn J. (J Biol Chem, 2017)
Mycobacterium tuberculosis and related Corynebacterineae synthesize a family of lipomannans (LM) and lipoarabinomannans (LAM) that are abundant components of the multilaminate cell wall and essential virulence factors in pathogenic species. Here we describe a new membrane protein, highly conserved in all Corynebacterineae, that is required for synthesis of full-length LM and LAM. Deletion of the Corynebacterium glutamicum NCgl2760 gene resulted in a complete loss of mature LM/LAM and the appearance of a truncated LM (t-LM). Complementation of the mutant with the NCgl2760 gene fully restored LM/LAM synthesis. Structural studies, including monosaccharide analysis, methylation linkage analysis, and mass spectrometry of native LM species, indicated that the ΔNCgl2760 t-LM comprised a series of short LM species (8–27 residues long) containing an α1–6-linked mannose backbone with greatly reduced α1–2-mannose side chains and no arabinose caps. The structure of the ΔNCgl2760 t-LM was similar to that of the t-LM produced by a C. glutamicum mutant lacking the mptA gene, encoding a membrane α1–6-mannosyltransferase involved in extending the α1–6-mannan backbone of LM intermediates. Interestingly, NCgl2760 lacks any motifs or homology to other proteins of known function. Attempts to delete the NCgl2760 orthologue in Mycobacterium smegmatis were unsuccessful, consistent with previous studies indicating that the M. tuberculosis orthologue, Rv0227c, is an essential gene. Together, these data suggest that NCgl2760/Rv0227c plays a critical role in the elongation of the mannan backbone of mycobacterial and corynebacterial LM, further highlighting the complexity of lipoglycan pathways of Corynebacterineae.